Fortalecer las habilidades y el aprendizaje de los saberes tradicionales, donde los niños experimenten y aprendan sobre su cultura (2021)
The Colombian educational system is made up of: initial education, preschool education, basic education (primary five grades and secondary four grades), middle education (two grades and culminates with a bachelor's degree), and higher education. In Colombia, education is defined as a process of permanent, personal, cultural and social training that is based on an integral conception of the person, their dignity, their rights and their duties. Is this educational system viable? It is what we have all asked ourselves for decades to rule ourselves by something that has not provided opportunities for the new developments and ideals of a new country. Generating gaps that could be corrected from the beginning of education. (Ministry of National Education, 2020)